Not of Woman Born : Representations of Caesarean Birth in Medieval and Renaissance Culture - Blumenfeld-Kosinski, Renate, 1952- (Book collections on Project MUSE., 1990)
Examines texts and visual images of caesarean birth and traces its history in medical writing and practice ; addresses the work of religious, ethical and cultural questions surrounding abdominal delivery in the Middle Ages and Renaissance.